2000
DOI: 10.1002/(sici)1099-0682(200005)2000:5<933::aid-ejic933>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of the Tetrachalcogenides [ME4(dppe)] (M = Pd, E = S; M = Pt, E = S, Se) with Activated Alkynes to Form Dithiolenes and Diselenolenes

Abstract: The tetrachalcogenides [ME4(dppe)] (M = Pd, E = S; M = Pt, E = S, Se) react with the activated alkynes RO2CC≡CCO2R (R = Me, Et) to form the dithiolenes and diselenolenes [M{E2C2(CO2R)2}(dppe)]; the structures of the compounds with E = S, R = Et have been determined by X‐ray crystallography; [PdS4(dppe)] also reacts with the carbene complex [W(CO)5{C(OEt)C≡CPh}] to yield the bimetallic dithiolene [Pd{S2C2[C(OEt)W(CO)5]Ph}(dppe)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Informationof bis(phosphane) platinum‐group metal complexesof bidentate organoselenium derivatives is rather sparse and is mainly concerned with Pt II complexes of diselenolsbearing aromatic fragments in the bridging moieties7 and complexes of diselenocarbonate derivatives8 or diselenolenes 9. Regarding Pd II 8a,9d,10 and Ni II 9a,11 bis(phosphane) complexes with bidentate organoselenium ligands, information is even sparser. Likewise, most of these complexes contain diselenocarbonate [8a,10a,10b,11d,11e] or diselenolene [9a,9d,10c–10g,11c–11e] derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Informationof bis(phosphane) platinum‐group metal complexesof bidentate organoselenium derivatives is rather sparse and is mainly concerned with Pt II complexes of diselenolsbearing aromatic fragments in the bridging moieties7 and complexes of diselenocarbonate derivatives8 or diselenolenes 9. Regarding Pd II 8a,9d,10 and Ni II 9a,11 bis(phosphane) complexes with bidentate organoselenium ligands, information is even sparser. Likewise, most of these complexes contain diselenocarbonate [8a,10a,10b,11d,11e] or diselenolene [9a,9d,10c–10g,11c–11e] derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…There are quite a few reports of platinum complexes containing selenium and phosphorus ligands, cis-P 2 PtSe 2 , and their NMR properties. 40,44,[50][51][52][53][54][55][56][57][58][59] For reasons of symmetry, most isotopomers of such complexes will constitute a higher-order spin system of type ABX 60,61 or of its limiting, non-existent, AA′X case. 62,63 Exceptions are the 31 P 2 and 31 P 2 , 195 Pt isotopomers and one 31 P 2 , 13 C isotopomer containing 13 C at the central CH 2 carbon of the dppp ligand.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…The magnitude of the 2 J( 77 Se, 31 P) coupling constants obtained here is in agreement with values found in the literature. 40,44,[50][51][52][53][54][55][56][57][58][59]66 For the compound that comes closest to 1 and 2, [Pt(PPh 3 ) 2 (1,2-Se 2 -1,2-C 2 B 10 H 10 ], Wrackmeyer et al reported that the values of the 2 J( 77 Se, 31 P) coupling constants for the cis and trans pathways are very similar, around 51 Hz. 50 This could actually indicate a dynamic process, converting the AA′X spin system into A 2 X, not observed for 1, 2.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…4 We have obtained spectroscopic evidence for similar behaviour by a bis(phosphine)platinum diselenolene. 5 We recently have reported that palladium diselenolenes may be readily prepared from Pd(0) phosphine complexes, using cyloalkeno-1,2,3-selenadiazoles or bis(cycloalkeno)-1,4-diselenins as the seleniumcontaining precursors. [6][7][8] Bridging chalcogen atoms in dinuclear metal complexes are known to be highly nucleophilic.…”
Section: Introductionmentioning
confidence: 99%
“…5 We recently have reported that palladium diselenolenes may be readily prepared from Pd(0) phosphine complexes, using cyloalkeno-1,2,3-selenadiazoles or bis(cycloalkeno)-1,4-diselenins as the seleniumcontaining precursors. [6][7][8] Bridging chalcogen atoms in dinuclear metal complexes are known to be highly nucleophilic. 9 Our investigations of the reactivity of dinuclear palladium diselenolenes therefore have begun with the study of their reactions with simple electrophiles such as alkyl halides, and the results are reported in this article.…”
Section: Introductionmentioning
confidence: 99%